1996
DOI: 10.1021/ja961920d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Hydratase from Rhodococcus rhodochrous J1 Contains a Non-Corrin Cobalt Ion with Two Sulfur Ligands

Abstract: We present spectroscopic data that show that a nitrile hydratase from Rhodococcus rhodochrous J1 is the first reported example of a native protein that contains a non-corrin Co 3+ ion with a mixed S and N(O) ligand field. Nitrile hydratases catalyze the addition of water to nitriles, yielding amides as the exclusive product, 3 and are used as industrial catalysts for the production of acrylamide. 4 The most thoroughly characterized nitrile hydratase is from Rhodococcus sp. R312 5 and is a (R ) 2 tetramer that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 21 publications
5
94
0
Order By: Relevance
“…Interestingly, the cobalt-containing cyanocobalamin is very efficient in catalyzing the reduction of 3NT, presumably by a mechanism similar to the reduction of the Co 3 + ion to Co 2 + by thiol-containing antioxidants. [39] These results suggest that protein tyrosine nitration in vivo is a redox-regulated process. Many important signaling cascades are regulated by redox states.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, the cobalt-containing cyanocobalamin is very efficient in catalyzing the reduction of 3NT, presumably by a mechanism similar to the reduction of the Co 3 + ion to Co 2 + by thiol-containing antioxidants. [39] These results suggest that protein tyrosine nitration in vivo is a redox-regulated process. Many important signaling cascades are regulated by redox states.…”
Section: Discussionmentioning
confidence: 89%
“…N-771 in the presence of ferric citrate in vitro has been observed (34). Cobalt exists as a non-corrin low-spin Co 3ϩ ion in H-NHase in R. rhodochrous J1 (40) and NHase in P. putida NRRL-18668 (7), suggesting that the holo-␣-subunit of L-NHase (holo-␣ 2 ␤ 2 ) and the holo-␣-subunit of holo-␣e 2 (which is the source of that of holo-␣ 2 ␤ 2 ) should also have a non-corrin low-spin Co 3ϩ ion. Therefore, the post-translational oxidation of the cysteine residues was associated with the oxidation of Co 2ϩ to Co 3ϩ , because Co 2ϩ was used as the cobalt donor in the in vitro experiments.…”
Section: Discussionmentioning
confidence: 97%
“…It is widely believed that the metal site structure of the cobalt-containing NHases is closely related with that of the iron-containing one. Indeed, recent ESR and extended x-ray absorption fine structure studies showed that the metal site of the NHase from Rhodococcus rhodochrous J1 was a mononuclear low-spin six-coordinate Co 3ϩ ion with the ligand field of mixed sulfur, and nitrogen or oxygen donor atoms (4).…”
mentioning
confidence: 99%